Muscarine-like compounds derived from a pyrolysis product of cellulose1. Issue 22 (14th June 2015) - Defant, Andrea; Mancini, Ines; Matucci, Rosanna; Bellucci, Cristina; Dosi, Federico; Malferrari, Danilo; Fabbri, Daniele
<x xml:space="preserve">Abstract</x> Starting from a hydroxylactone anhydrosugar available from catalytic cellulose pyrolysis, five new muscarine-like compounds have been synthesized and studied for their binding affinity to human subtype muscarine receptors, obtaining results supported by docking calculation.